Inovação aberta e justiça digital: transformação disruptiva do judiciário por meio da colaboração com empresas startups - Vieira, Thiago Gontijo (2023)
This master's thesis in Law appreciates the modernization process implemented by the Brazilian Judiciary since the covid-19 pandemic, with emphasis on the Justice 4.0 Program, which has advanced in the virtualization of judicial services and in the adoption of governance practices, resulting in expanded Access to Justice. Despite the progress, however, it is exposed that (i) the historical situation of overload, congestion and slowness of the judicial system has not yet been overcome, nor even (ii) the condition of fragmentation, overlap and duplicity of the policy of computerization of the cases. This reality prevents the adoption of data-driven models, as well as compromises the efficient use of automation and artificial intelligence technologies, hindering the efficient management of binding precedents. The absence of correlation between modernization initiatives and the indicators of efficiency and expeditious processing is a consequence of the closed innovation practices of the Judiciary, restricted to the knowledge and technologies developed internally, with predominant participation of judges and public offices. It is maintained that the adoption of open innovation models – through entrepreneurial collaborations with private companies, especially startups – will enable the effective transformation of Justice, in a disruptive way, with a view to improving its results and ameliorating the quality of jurisdictional services. Besides that, it was identified, from the Normative Framework of Innovation, that the public administration has an obligation to promote innovation, both by instruments to stimulate entrepreneurship, as by innovative actions in collaboration with the private environment. The research adopts an interdisciplinary approach between Law, Technology and Administration. In relation to the research techniques, it was used the hypothetical-deductive method, with the following methodological procedures: (i) empirical analysis of statistical data; (ii) study of normative acts and institutional publications; and (iii) bibliographic review of publications in the indicated areas. As a result, it was systematized the Open Innovation Support Model, which can be adopted by leaders and public managers of the Brazilian National Justice Council, other councils, courts, and judicial bodies as a reference for the promotion of innovative collaborations with private companies, especially startups, with the objective of implementing disruptive processes, products and services that generate benefits for the whole society. As a vision of the future, it is expected to contribute to the promotion of a culture of open innovation throughout the public sector.